Effects of caffeine withdrawal and withdrawal recovery on alertness and working memory performance among undergraduate students - Dagur Andri Einarsson 1998- (2020)
Þessi rannsókn skoðaði áhrif koffínfráhvarfa á vinnsluminnisspönn og árverkni. Þátttakendur í rannsókninni voru nemar við Háskólann í Reykjavík vorið 2020. Aldur þátttakenda var á bilinu 20 til 31 árs og voru 4 konur og 3 karlar sem tóku þátt í rannsókninni. Núverandi rannsókn notaðist við endurteknar mælingar þar sem tveir aðskildir hópar fengu annaðhvort kaffi með eða án koffíns. Þátttakendur tóku rafræn hugræn próf sem mældu vinnsluminnisspönn annars vegar og árverkni hins vegar á ákveðnum prófdögum. Fyrsta mæling var grunnlínumæling sem fór fram á miðvikudegi, önnur mælingin fór fram daginn eftir til þess að skoða áhrif fráhvarfa og sú þriðja sex dögum eftir aðra mælingu til þess að skoða áhrif endurheimtar eftir fráhvörf á frammistöðu. Allar niðurstöður reyndust ómarktækar. Lykilorð: Vinnsluminni, Árverkni, Koffín, Fráhvörf The current study aimed to examine effects of caffeine withdrawal on working memory span and psychomotor vigilance. Participants in the study were college students attending Reykjavík University during the spring semester of 2020. Participants were between the ages of 20 and 31 and the group consisted of 4 females and 3 males. A repeated measures design was used, with two separate groups either receiving caffeinated coffee or decaffeinated coffee. Participants completed an automated operation span task (Aospan) and psychomotor vigilance test (PVT) once per day on three testing days. The first testing day was a baseline measurement conducted on a Wednesday, the second measurement was conducted the morning after baseline testing to examine withdrawal effects. The third measurement was conducted 6 days after the second one to examine performance after recovery from withdrawal effects. Results indicated no significant differences on any measurements. Keywords: Working Memory, Alertness, Caffeine, Withdrawal